Combinatorial one-pot chemoenzymatic synthesis of heparin. (20th May 2015) - Bhaskar, Ujjwal; Li, Guoyun; Fu, Li; Onishi, Akihiro; Suflita, Mathew; Dordick, Jonathan S.; Linhardt, Robert J.
Highlights: A simple one pot method for heparin synthesis. Bioengineered heparin with activity similar to USP heparin. 2- O -sulfation must occur before 6- O -sulfation. Abstract: Contamination in heparin batches during early 2008 has resulted in a significant effort to develop a safer bioengineered heparin using bacterial capsular polysaccharide heparosan and recombinant enzymes derived from the heparin/heparan sulfate biosynthetic pathway. This requires controlled chemical N -deacetylation/ N -sulfonation of heparosan followed by epimerization of most of its glucuronic acid residues to iduronic acid and O -sulfation of the C2 position of iduronic acid and the C3 and C6 positions of the glucosamine residues. A combinatorial study of multi-enzyme, one-pot, in vitro biocatalytic synthesis, carried out in tandem with sensitive analytical techniques, reveals controlled structural changes leading to heparin products similar to animal-derived heparin active pharmaceutical ingredients. Liquid chromatography–mass spectrometry and nuclear magnetic resonance spectroscopy analysis confirms an abundance of heparin's characteristic trisulfated disaccharide, as well as 3- O -sulfo containing residues critical for heparin binding to antithrombin III and its anticoagulant activity. The bioengineered heparins prepared using this simplified one-pot chemoenzymatic synthesis also show in vitro anticoagulant activity.